Efficacy of remote dielectric sensing (ReDS) in the prevention of heart failure rehospitalizations: a meta-analysis. Issue 5 (3rd September 2021) - Sattar, Yasar; Zghouzi, Mohamed; Suleiman, Abdul-Rahman M.; Sheikh, Amaan; Kupferman, Judah; Sarfraz, Azza; Arshad, Junaid; Mir, Tanveer; Ullah, Waqas; Pacha, Homam Moussa; Thakkar, Samarthkumar; Elgendy, Islam Y; et al.
ABSTRACT: The clinical efficacy of remote dielectric sensing (ReDS) monitoring is not well known. Digital databases were searched to identify relevant articles. Pooled unadjusted odds ratio (OR) for dichotomous outcomes were calculated using a random-effects model. Findings were reported as a point estimate with its 95% confidence interval (CI). A total of 985 patients across seven studies were included in the meta-analysis. Patients with heart failure monitored with ReDS had significantly lower odds of hospital readmission compared with non-ReDS patients (OR = 0.40; 95% CI 0.29–0.56; z = 5.43 p = 0.000, I2 = 0%). Subgroup analysis based on the duration of follow-up showed a lower odd of readmission within 30 days (OR = 0.36; 95% CI 0.18–0.71; z = 2.93; p = 0.003; I2 5.7%), as well as between 1 and 3 months (OR = 0.42; 95% CI 0.29–0.61; z = 4.54; p = 0.000; I2 = 0.0%). ReDS effect of lower readmissions of HF was observed irrespective of the duration of follow-up (<1-month vs 1–3 months). ReDS monitoring significantly lowers the odds of HF readmission within 3 months compared to participants not using ReDS.